Polysulfone Hollow Porous Granules Prepared from Wastes of Ultrafiltration Membranes as Sustainable Adsorbent for Water and Air Remediation. (21st June 2017) - Zambianchi, Massimo; Aluigi, Annalisa; Capobianco, Massimo Luigi; Corticelli, Franco; Elmi, Ivan; Zampolli, Stefano; Stante, Francesco; Bocchi, Letizia; Belosi, Franco; Navacchia, Maria Luisa; Melucci, Manuela
Abstract : Polysulfone hollow fibers (PS‐HF) are widely used in ultrafiltration modules for hemodialysis and drinking water purification for the removal of large colloids, microbes, and viruses. The preparation of commercial PS‐HF standard modules leads to the generation of PS‐HF scraps in amount higher than 5% of the total production (tons scale) that cannot be used for filtration purposes and represent large volume plastic wastes. Here, a simple approach to convert such high value waste into a new granular material with excellent adsorption properties toward organic compounds is introduced. Polysulfone hollow porous granules (PS‐HPG) are prepared by a mechanical grinding process and then exploited for the removal of selected organic compounds from water under flow and batch conditions. Volatile organic compounds (VOCs), polycyclic aromatic hydrocarbons, and also selected emerging organic contaminants (EOCs), including two common drugs (carbamazepine and diclofenac), a plastic additive (bisphenol A), and a textile dye (Rhodamine B), are successfully adsorbed. Regeneration and reuse possibility of PS‐HPG are also demonstrated. Additionally, air remediation from VOCs and from airborne nanoparticles is successfully achieved by flowing an air stream through a filtration cartridge filled by PS‐HPG. Abstract : Hollow polysulfone porous granules (PS‐HPG) are prepared by mechanical grinding of polysulfone hollow fiber membrane industrial wastes. PS‐HPG is an efficient and reusable adsorbant for the removal of several organic compounds of environmental concern from water and air. Aerosol nanoparticles retention capability is also demonstrated, highlighting the efficacy of PS‐HPG for combined adsorption and filtration purposes.